2014
DOI: 10.1080/10942912.2013.837065
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sterol Composition of Hazelnut During Fruit Development

Abstract: Hazelnut is a valuable source of fat-soluble bioactive components. Among the fat-soluble bioactive components, phytosterols have gained much interest due to their cholesterol reducing properties. This study presents the evaluation of changes in the sterol composition of Turkish hazelnut cultivars (Tombul, Palaz, and Sivri) during fruit development. Three major sterols (β-sitosterol, campesterol, and Δ5-avenasterol), and five minor sterols (clerosterol, brassicasterol, stigmasterol, Δ7-stigmastenol, and Δ7-aven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
2
6
0
1
Order By: Relevance
“…Sterol is one of the most important bioactive compounds presenting in vegetable oils. It is an essential component of cell membrane and effective in lowering total and low density lipoprotein cholesterol level, reducing the risk of heart disease and certain cancer (Ilyasoglu, ). The change in sterol composition of kenaf seed oil during accelerated storage is presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Sterol is one of the most important bioactive compounds presenting in vegetable oils. It is an essential component of cell membrane and effective in lowering total and low density lipoprotein cholesterol level, reducing the risk of heart disease and certain cancer (Ilyasoglu, ). The change in sterol composition of kenaf seed oil during accelerated storage is presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Protein content decreased in general at the final harvest time (H7) as compared to the first harvest time (H1) (Table 1). Ilyasoglu (2015) and Seyhan et al (2007) reported that the protein contents in 'Tombul', 'Palaz', 'Badem' and 'Sivri' cultivars decreased as the harvest time progressed. Cristofori et al (2015), on the other hand, stated that the protein content in the 'Tonda Gentile Romana' cultivar fluctuated as the harvest time progressed.…”
Section: Protein Contentmentioning
confidence: 99%
“…The unsaponifiable fraction is mostly characterized by sterols, which differ in composition between cultivars and geographical origin, and decreases along with the shelf-life (Amaral et al, 2006 ; Ilyasoglu, 2015 ; Ghisoni et al, 2020 ). The three most abundant sterols are β-sitosterol, accounting for 85% of the total content, campesterol at 5–7%, and Δ5-avenasterol, which achieves on average 2–4% of the total composition (Ilyasoglu, 2015 ).…”
Section: Hazelnuts Composition and Its Correlation To Sensory Propertiesmentioning
confidence: 99%
“…The unsaponifiable fraction is mostly characterized by sterols, which differ in composition between cultivars and geographical origin, and decreases along with the shelf-life (Amaral et al, 2006 ; Ilyasoglu, 2015 ; Ghisoni et al, 2020 ). The three most abundant sterols are β-sitosterol, accounting for 85% of the total content, campesterol at 5–7%, and Δ5-avenasterol, which achieves on average 2–4% of the total composition (Ilyasoglu, 2015 ). The sterol fraction plays an important role in authentication and frauds counteraction, it is used to identify olive oils adulterated with hazelnut oils of lower quality (Parcerisa et al, 1999 ; Zabaras and Gordon, 2004 ), as it might be further used in the discrimination of different hazelnut cultivars (Ghisoni et al, 2020 ).…”
Section: Hazelnuts Composition and Its Correlation To Sensory Propertiesmentioning
confidence: 99%